2012
DOI: 10.1016/j.rbmo.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heparin on the outcome of IVF treatment: a systematic review and meta-analysis

Abstract: The effect of heparin on IVF outcome has been widely debated in the literature. A systematic review and meta-analysis of the published literature was conducted to evaluate the effect of heparin treatment on IVF outcome. Searches were conducted on MEDLINE, EMBASE, Cochrane Library and Web of Science and identified 10 relevant studies (five observational and five randomized) comprising 1217 and 732 IVF cycles, respectively. The randomized studies included small numbers of women and exhibited high methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
(96 reference statements)
0
30
0
2
Order By: Relevance
“…Unfractionated heparin as well as LMWH is able to modulate the process of decidualization, potentially improving implantation success in ART conceived pregnancies, as well as, clinical pregnancy rates [14,15]. Regarding the effects of antithrombotic treatment in pregnancies conceived by ART, the majority of research to date has focused on three primary outcomes: implantation rate, clinical pregnancy rate, and live birth rate [16,17]. As a consequence, the body of research to date has not addressed the effect of antithrombotic treatment on specific aspects of perinatal outcomes, which are known factors associated with maternal, fetal and neonatal wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Unfractionated heparin as well as LMWH is able to modulate the process of decidualization, potentially improving implantation success in ART conceived pregnancies, as well as, clinical pregnancy rates [14,15]. Regarding the effects of antithrombotic treatment in pregnancies conceived by ART, the majority of research to date has focused on three primary outcomes: implantation rate, clinical pregnancy rate, and live birth rate [16,17]. As a consequence, the body of research to date has not addressed the effect of antithrombotic treatment on specific aspects of perinatal outcomes, which are known factors associated with maternal, fetal and neonatal wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that there is no evidence regarding the efficacy of heparin either in women with two or more consecutive previous pregnancy losses [30] or in those with unexplained recurrent miscarriage [31] or in women with inherited thrombophilia (TanWK). Also Seshadri et al [32] in their meta-analysis including 10 relevant studies (five observational and five randomized) did not observe any difference analysing only randomized studies with regard to clinical pregnancy rate (RR 1.23, 95% CI 0.97-1.57), live birth rate (RR 1.27, 95% CI 0.89-1.81) implantation rate (RR 1.39, 95% CI 0.96-2.01) and miscarriage rate (RR 0.77, 95% CI 0.24-2.42) between women receiving heparin compared to placebo during IVF treatment. On the contrary, a systematic review and a meta-analysis including two RCTs and one quasi-randomized trial showed a significant improvement in the LBR (risk ratio (RR) ¼ 1.79, 95% confidence interval (CI) ¼ 1.10-2.90, P ¼ 0.02) and a reduction in the miscarriage rate (RR ¼ 0.22, 95% CI ¼ 0.06-0.78, P ¼ 0.02) with LMWH compared with controls.…”
Section: Heparinmentioning
confidence: 97%
“…After pooling the results, randomized studies showed no difference in the CPR (RR 1.23, 95% CI 0.97 -1.57), LBR (RR 1.27, 95% CI 0.89 -1.81) and IR (RR 1.39, 95% CI 0.96 -2.01) and abortion rate (RR 0.77, 95% CI 0.24 -2.42). However, this review was highly susceptible to publication bias secondary to the high methodological heterogeneity between the trials in which heparin's effect was assessed irrespective of the failed cycles, small numbers of women included with considerable difference in the administered formulations, dosing, timing of onset and duration of therapy [61].…”
Section: ) Inherited Thrombophiliamentioning
confidence: 99%